ANALISIS KINERJA INDUSTRI ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PENDEKATAN RASIO PROFITABILITAS - Yulis Nurul Aini; Agustin Dwi Haryanti; Khoriyah Trianti (Jurnal Akademi Akuntansi, 2021)
ABSTRACTS This study aims to: 1. Understand how the performance of the cigarette industry in the Indonesia Capital Market. 2. Understand about the best performance among the cigarette industry. The research data was obtained from published on the Indonesia Stock Exchange and information company website in the form of financial reports for the period 2018-2020. The financial statement are analyzed using profitability ratios to explain the performance of each cigarette industry. The Profitability ratio used are ROE, ROA, NPM, and GPM. The data analysis method is descriptive and comparative by comparing the results of the calculation of the profitability ratios with the industry average standart. The result of this study indicate performance of cigarette industry was very good, except for PT. Bentoel Internasional Investama, Tbk and the best performance is PT PT. Hanjaya Mandala Sampoerna Tbk.